Pengaruh E-Marketing, E-Worm, Dan Promosi Terhadap Brand Awareness Serta Pengaruhnya Terhadap Keputusan Beli Jasa Startup (Studi Kasus Grab) - Adrian Pratama Putra; Heri Kuswanto (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
The purpose of this research is to know the influence between E-Worm, e-marketing, promotion, brand awareness, and the decision to buy services at GRAB startup. Analysis is used with data Structure Equation Modeling technique with AMOS 24. Conclusion of analysis result show that promotion variable and brand awareness have a positive and significant influence on purchasing decisions, while E-Worm and e-marketing variables do not affect the decision to buy GRAB startup services. Thus, GRAB can pay attention to promotional factors increase brand awareness and consumer purchasing decisions and increase the influence of e-marketing and e- wom to further strengthen the influence to consumers.